A robust test for weak instruments with multiple endogenous regressors - Lewis, Daniel J.,Mertens, Karel (Federal Reserve Bank of New York, 2022)
We extend the popular bias-based test of Stock and Yogo (2005) for instrument strength in linear instrumental variables regressions with multiple endogenous regressors to be robust to heteroskedasticity and autocorrelation. Equivalently, we extend the robust test of Montiel Olea and Pflueger (2013) for one endogenous regressor to the general case with multiple endogenous regressors. We describe a simple procedure for applied researchers to conduct our generalized first-stage test of instrument strength and provide efficient and easy-to-use Matlab code for its implementation. We demonstrate our testing procedures by considering the estimation of the state-dependent effects of fiscal policy as in Ramey and Zubairy (2018).
10419/266104
Keywords: Graue Literatur; instrumental variables; weak instruments test; multiple endogenous regressors; heteroskedasticity; serial correlation